Diversity in the Dark: Bat Fauna from Prince Mohammed Bin Salman Royal Reserve - Hannah Haggon; David White; Joshua Smithson; David Wells; Ricardo Oliveira Ramalho (Diversity)
Prince Mohammed bin Salman Royal Reserve (PMBSRR or the Reserve) is located in the northwest of Saudi Arabia and covers an area of 24,500 km2 of both marine and terrestrial ecosystems. Bat surveys have been undertaken between 2022 and 2024 across PMBSRR as part of the Reserve’s groundbreaking conservation efforts and this is the first published checklist of the bat species present within the Reserve. Survey methods included bat capture, roost inspection, and acoustic recordings. Tissue and faecal samples were taken during the surveys and compared to a global database to confirm the species present. The survey results confirmed the presence of 18 species belonging to 14 genera of eight families. This research has greatly expanded our knowledge on the diversity of bats within the Kingdom, increasing the reported bat species in the Tabuk region by seven species, with the addition of Rhyneptesicus nasutus, Rhinolophus hipposideros, Nycteris thebaica, Tadarida aegyptiaca, Rhinopoma microphyllum, Taphozous nudiventris, and Taphozous perforatus and increasing the number of species within Saudi Arabia by one species, with the addition of Vansonia rueppellii.